Influence of high pressure on the solubility of ribavirin in six pure solvents from 283.15 to 323.15 K. (December 2022) - Feng, Yaoguang; Hao, Hongxun; Tian, Beiqian; Chen, Kui; Wang, Na; Wang, Ting; Huang, Xin
Highlights: Solubility data of ribavirin in six pure solvents at 9.0 MPa and 0.1 MPa was measured. Solvation free energy of ribavirin in six solvents at two pressures was calculated. The experimental solubility data were correlated by different models. The solubility data and the NRTL model were used to calculate the mixing and dissolution thermodynamic properties. Abstract: The solubility of ribavirin in six pure solvents was measured at 9.0 MPa and 0.1 MPa to evaluate the influence of high pressure on solubility at the temperature range from 283.15 K to 323.15 K. The results indicated that all the solubilities of ribavirin decreased slightly at 9.0 MPa compared with those at 0.1 MPa. Solvation free energy of ribavirin in six solvents under two pressures was calculated to explain the decrease of solubility under high pressure. Besides, the solubility of ribavirin increased with the rising temperature under both 0.1 MPa and 9.0 MPa. Furthermore, the experimental solubility data under two pressures were correlated by the modified Apelblat equation and NRTL model. The average relative deviation (ARD%) value of the modified Apelblat equation is less than 3 %, which can give better correlation results. Finally, the thermodynamic properties of mixing and dissolution of ribavirin in six pure solvents under two pressures were also calculated based on the solubility experimental data and the NRTL equation.